FIQH SIYASAH DALAM PERSPEKTIF AL-QUR’AN DAN AL-HADIST - Wahyu Abdul Jafar (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2018)
Abstract: The study of fiqh Siyasah is a very urgent and warm to discussed, because it is related to politics that regulate the lives of many people. Therefore, it is necessary to know in detail what Siyasah fiqh is so that it is not trapped and erroneous in making political policies based on maslahah. Islamic Siyasah based on maslahah is siyasah born of al-quran and hadith not siyasah born of the interests of certain individuals or groups. It is this Islamic Siyasah which is the object of study of the Siyasah fiqh. This object needs to be clarified so as not to misunderstand Islamic politics or politicized Islam. The impression of politics is dirty and bad indeed, it is inherent in the minds of the people. This is as a result of the bad politicians themselves. Many political figures have been caught in the case of corruption even though they are from islam political parties. It is here that it is very important to distinguish between Islamic politicians and Islamic politics itself. In order to find out the policies or actions of Islamic political figures that are not in accordance with the siyasah fiqh, the policy or action cannot be categorized as siyasah syar'iyah even though the policy comes from party political figures with Islamic labels. Keywords : Al-Hadist, Al-Qur’an Dan Fiqh Siyasah